1994
DOI: 10.1007/bf00024028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ogura male-sterile cytoplasm on the performance of cabbage hybrid variety

Abstract: Cabbage hybrid seeds are commercially produced by means of self-incompatibility. This system may show some instability mainly under tropical conditions, where cytoplasmic male sterility can be an alternative approach for hybrid seeds production . However, cabbage hybrids holding Ogura male-sterile cytoplasm show some irregularities during development. By assessing some characteristics during the growing cycle of male-sterile cabbage hybrids and comparing them to genomic similar male-fertile ones and to the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Homogeneous germination was carefully controlled in order to avoid any maternal effects on germination due to maternal tissues. However, some interaction between the Ogura male sterile cytoplasm and the hoary mustard nuclear genome cannot be discounted, but is considered to be unlikely since no effect had been detected in other work with the same cytoplasm (de Melo & Giordano 1994 the hybrid never appeared with lower competitive ability than hoary mustard. A similar trend has recently been found for hybrids between sugar beet and wild sea beet (Fredshavn & Poulsen 1995) and between weedy and cultivated radishes (Klinger & Ellstrand 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Homogeneous germination was carefully controlled in order to avoid any maternal effects on germination due to maternal tissues. However, some interaction between the Ogura male sterile cytoplasm and the hoary mustard nuclear genome cannot be discounted, but is considered to be unlikely since no effect had been detected in other work with the same cytoplasm (de Melo & Giordano 1994 the hybrid never appeared with lower competitive ability than hoary mustard. A similar trend has recently been found for hybrids between sugar beet and wild sea beet (Fredshavn & Poulsen 1995) and between weedy and cultivated radishes (Klinger & Ellstrand 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Dey et al (2011) have reported that chloroplast substituted Ogura cytoplasm does not affect vegetative and commercial traits significantly; however, floral and reproductive traits were influenced considerably in cauliflower. The effect of Ogura cytoplasm introgression on agronomic traits of cabbage has already been reported by Melo and Giordano (1994). However, effect of this alien cytoplasm on nutritional quality of cabbage is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Such nuclear-organellar incompatibilities led in some somatic hybrids to disturbances in habit or flower traits such as male sterility, necroses or a low nectar secretion, e.g. in the Ogura system , Ceiis and Jourdan 1993, de Melo and de Giordano 1994.…”
Section: Discussionmentioning
confidence: 99%